Peningkatan Kesadaran Sejarah Masyarakat Melalui Sejarah Publik - A, Dian (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The changing times have made many things, including public history, develop quite rapidly. Public history is one of the instruments for developing public understanding of historical awareness, given that many events are difficult to predict these days. The public also needs to be given an understanding of the importance of historical awareness so that they can learn more about past events and be able to make decisions today and shape the future. Therefore, for an activist, educator, or community who has a concentration on history, it needs to be developed further so that the public can directly participate in these studies and discussions. For this reason, the development of history needs to be improved so that the community can access more services regarding matters related to history. Thus, if people's understanding of history is much more mature, then people's intelligence regarding past events will be a lesson in the future.